Digital Transformation and Circular Economy in Mine Tailings Management: A Multi-Country Review of Emerging Practices - Aridaman Walia; Martin Anda; Jonathan Whale; Om Dubey (Circular Economy and Sustainability, 2026)
Mine tailings present a growing global environmental and economic challenge requiring integrated technological, regulatory, and circular economy responses. This review examines international trends in tailings management, with particular focus on Western Australia, drawing on comparative evidence from Brazil, Chile, South Africa, Canada, and Finland. It analyses digital innovations (AI, IoT, blockchain, UAVs) alongside circular economy strategies, evaluates regulatory frameworks, and identifies key research gaps in economic assessment, long-term environmental monitoring, technological integration, and community engagement. Western Australia is identified as well-positioned to lead responsible tailings management, with lessons applicable across the global mining sector.

Simulation and techno-economic study of Botryococcus Braunii biofilm cultivation for biofuel production in tropical drylands, Indonesia - Nugroho Adi Sasongko; Risa S. Wijihastuti; Ryozo Noguchi; Navid R. Moheimani; Parisa A. Bahri; Martin Anda; Mitsutoshi Nakajima; Arief A. R. Setiawan; Nadirah Nadirah; Rudi Herdioso; Gian A. Pertiwi; Tri Handayani; et al. (Energy, Ecology and Environment, 2026)

Edible plates from wheat bran and blackcurrant pomace: A multidisciplinary approach to by-product valorization - Vitalijs Radenkovs; Karina Juhnevica-Radenkova; Paweł Górnaś; Dmitrijs Jakovlevs; Martins Andzs; Inta Krasnova; Daniels Udalovs; Ingmars Cinkmanis; Jorens Kviesis; Anda Valdovska; Dalija Seglina (Journal of Cleaner Production, 2026)

Pulmonary exposure to renewable diesel exhaust particles alters protein expression and toxicity profiles in bronchoalveolar lavage fluid and plasma of mice - Sarah McCarrick; Vilhelm Malmborg; Louise Gren; Pernille Høgh Danielsen; Martin Tunér; Lena Palmberg; Karin Broberg; Joakim Pagels; Ulla Vogel; Anda R. Gliga (Archives of Toxicology, 2025)
Exposure to diesel exhaust is associated with increased risk of cardiovascular and lung disease. Substituting petroleum diesel with renewable diesel can alter emission properties but the potential health effects remain unclear. This study aimed to explore toxicity and underlying mechanisms of diesel exhaust from renewable fuels. Using proximity extension assay (Olink), 92 proteins linked to inflammation, cardiovascular function, and cancer were analyzed in bronchoalveolar lavage fluid (BALF) and plasma in mice 1 day after pulmonary exposure to exhaust particles at doses of 6, 18, and 54 µg/mouse. Particles were generated from combustion of renewable (rapeseed methyl ester, RME13, hydrogen-treated vegetable oil, HVO13; both at 13% O 2 engine intake) and petroleum diesel (MK1 ultra-low-sulfur diesel at 13% and 17% O 2 intake; DEP13 and DEP17). We identified positive dose–response relationships between exposure and proteins in BALF using linear models: 33 proteins for HVO13, 24 for DEP17, 22 for DEP13, and 12 for RME13 ( p value e.g., CCL2, CXCL1, CCL3L3, CSF2, IL1A) correlated ( r s ≥ 0.5) with neutrophil cell count and DNA damage in BAL cells. Interestingly, plasma protein profiles were only affected by RME13 and, to lesser extent, by DEP13. Overall, we identified inflammation-related changes in the BALF as a common toxic mechanism for the combustion particles. Our protein-based approach enables sensitive detection of inflammatory protein changes across different matrices enhancing understanding of exhaust particle toxicity.

Utilization and integration of microalgae consortium in treating undiluted anaerobic digestate animal effluent to produce animal feed, bio-oil, and biogas - Nugroho Adi Sasongko; Jeremy Ayre; Ryozo Noguchi; Navid R. Moheimani; Parisa A. Bahri; Martin Anda; Mitsutoshi Nakajima; Ernie S.A. Soekotjo; Gian Aditya Pertiwi; Tri Handayani; Soen Steven (Bioresource Technology, 2025)

Evaluating the environmental impacts of land use change in the conservation area of Indonesian National Park using life cycle assessment - Anisah Anisah; Yoyon Wahyono; Novy Ariyanto; Nugroho Adi Sasongko; Isnaeni Kumalasari; Virny Zasyana Eka Putri; Martin Anda; Mutia Citrawati Lestari; Lambas Parlaungan Panggabean; Rohmadi Ridlo; Sundari Sundari; Anissa Dewi Suryaningtyas; et al. (Regional Studies in Marine Science, 2024)

Effect of spinal cord injury on the skin temperature of different regions of interest during a graded exercise test in a moderate temperature environment - Jose Luis Sanchez-Jimenez; Rosa M. Cibrian-Ortiz de Anda; Maria Vazquez-Fariñas; Soraya Martin-Manjarres; Jose Ignacio Priego-Quesada; Inmaculada Aparicio-Aparicio (Journal of Thermal Biology, 2024)

A monitoring of environmental effects from household greywater reuse for garden irrigation - Radin Maya Saphira Radin Mohamed; Amir Hashim Mohd. Kassim; Martin Anda; Stewart Dallas (Environmental Monitoring and Assessment, 2013)